Manajemen Pendidikan Islam di Pondok Pesantren Al-‘Ashr Al-Madani Sindanglaya - Nurhanifia, Fadhlin; Yusrina, Alya; Azmi, Fadhilah Hurul; Satuki, Irsyad Arnald; Faqih, Rafi Ahmad; Latiefah, Elsabila Millaty; Maulana, Dika Irfan; Salam, Mochamad Fadlani (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study aims to describe the implementation of excellent school management at Pondok Pesantren Al ‘Ashr Al Madani. A qualitative approach was used with data collection techniques including observation and interviews with the principal (Al-Mudir) and the Head of Administration. The results show that the pesantren applies integrated and structured management across several areas: human resources, technology, facilities and infrastructure, financing, curriculum, and health services. Each aspect is implemented based on Islamic values, independence, and educational quality. The use of computer laboratories, a competency-based curriculum, and support from business units and agricultural land reflect managerial innovation. Involving students in maintaining facilities also strengthens character education. The study concludes that a value-based, integrated management approach can serve as a model for developing excellent schools in pesantren settings. The study recommends strengthening technological supervision and continuous professional development for educators.